Snacking in Japanese nursery school children aged 3–6 years: its characteristics and contribution to overall dietary intake. Issue 5 (11th April 2021) - Tajima, Ryoko; Murakami, Kentaro; Asakura, Keiko; Fujiwara, Aya; Uechi, Ken; Sugimoto, Minami; Wang, Han-Chieh; Masayasu, Shizuko; Sasaki, Satoshi
Abstract: Objective: This cross-sectional study evaluated the dietary characteristics of snacks, the contribution of snacks to daily nutrient intake and the association of energy intake (EI) from snacks with the prevalence of nutritional inadequacy in Japanese nursery school children. Design: Foods and nutrients consumed in each eating occasion were assessed by 3-d dietary records. The prevalence of inadequate intake of twenty nutrients assessed by the age- and sex-specific reference values in the Japanese Dietary Reference Intakes was compared according to tertile categories of EI from snacks. Setting: A multi-regional dietary survey based on nursery schools in Japan. Participants: A total of 187 boys and 191 girls aged 3–6 years. Results: EI from snacks accounted for 19·5 % (sd 6·9) of total daily EI. Confectionaries accounted for the largest part of EI from snacks (35·3 %), followed by milk (19·5 %). Relative to their energy contribution, snacks accounted for a small proportion for all nutrients examined, except for free sugar, calcium, SFA and riboflavin. Although a higher EI from snacks was associated with favourable profiles for intakes of calcium, iron, thiamine and riboflavin, excessive intakes of free sugar and Na were more prevalent among children with a higher EI from snacks. Conclusions: Although snacks are effective in meeting the requirement of some nutrients among Japanese nursery school children, snacks are generally not nutrient-dense and have an impact on excessive intake of some nutrients. There is hence room for improvement in food choices at snack time.